Hubungan antara Motivasi Menulis dan Penguasaan Diksi dengan Keterampilan Menulis Laporan - Muhammad Arief Nurrohman; St Y Slamet; Tri Budiharto (Didaktika Dwija Indria, 2021)
Abstract. This study aims to 1) know whether or not there is a relationship between writing motivation and report writing skills; 2) knowing whether or not there is a relationship between mastery of diction and report writing skills; 3) know whether or not there is a relationship between writing motivation and mastery of diction together with report writing skills. The research was conducted using correlational methods. Data collection techniques using tests and questionnaires. The data analysis techniques used in this study were simple correlation analysis and double correlation analysis. Based on the results of data analysis it can be concluded that 1) there is a significant relationship between writing motivation and report writing skills namely coefficient of correlation r count (0.99) > r table (0.17) with t count significance (108.33) > t table (1.65); there is a significant relationship between diction mastery and report writing skills i.e. coefficient of correlation r count (0.97) > r table (0.17) with t count significance (50.93) > t table (1.65); there is a significant relationship between writing motivation and diction mastery together with report writing skills namely r count (0.99) > r table (0.17), F count significance (4396.54) > F table (3.07) with a real level á = 0.05 and df 128.Keywords: writing motivation, diction mastery, report writing skills, elementary school